PERANAN DINASTI IDRISIYAH DALAM PENYEBARAN SYI’AH DI MAROKO 172-314 H/789-926 M - Marwan Marwan; Padila Padila (Tanjak: Sejarah dan Peradaban Islam, 1970)
This study aims to determine the progress of Muslims in the role of the Idrisiyah dynasty in the spread of Shi'ism in Morocco, to answer the question How is the history of Shi'ism and its spread in Morocco and What is the Role of the Idrisiyah dynasty in the spread of Shi'ism in Morocco. In this thesis it can be found that it is concluded that Idris bin Abdullah or often called Idris I is the founder of the Idrisiyah dynasty, he is the grandson of Hasan who is the son of Fatimah and the grandson of Muhammad SAW. The Idrisiyah dynasty was founded in 172 H/789 H